2007
DOI: 10.1002/jcc.20859
|View full text |Cite
|
Sign up to set email alerts
|

On the applicability of multireference second‐order perturbation theory to study weak magnetic coupling in molecular complexes

Abstract: The performance of multiconfigurational second-order perturbation techniques is established for the calculation of small magnetic couplings in heterobinuclear complexes. Whereas CASPT2 gives satisfactory results for relatively strong magnetic couplings, the method shows important deviations from the expected Heisenberg spectrum for couplings smaller than 15-20 cm(-1). The standard choice of the zeroth-order CASPT2 Hamiltonian is compared to alternative definitions published in the literature and the stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 74 publications
2
101
0
Order By: Relevance
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 91%
See 1 more Smart Citation
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 91%
“…So far, the DDCI approach has been extensively employed in the evaluation of J in molecular and solid state magnetic materials with a remarkable good agreement with experiment. [20][21][22][23][24][25][26][27][28][29][30][31][32] Some years ago we took benefit of this methodology to analyze in depth the physical contributions to the magnetic coupling on a series of binuclear Cu ͑II͒ complexes. 33 The use of the DDCI strategy allows not only to obtain quite accurate J values but also to analyze the various physical effects by generating CI spaces of increasing lengths that include different types of determinants.…”
Section: Introductionmentioning
confidence: 99%
“…The method gave excellent results for a series of binuclear Ni II complexes [50] and a hetero binuclear complex with Ni II and Cr III , [51] but is not as general applicable as foreseen. [52] Localized orbitals Accurate calculations are a necessary but not sufficient condition to obtain useful results from a quantum chemical study.…”
Section: Projected Orbitalsmentioning
confidence: 98%
“…Di↵erent methods are now available for the computational interpretation and analysis of the magnetic data, most of them based on the density functional theory UNIVERSITAT ROVIRA I VIRGILI FROM MONONUCLEAR TO DINUCLEAR: MAGNETIC PROPERTIES OF TRANSITION METAL COMPLEXES Sergi Saureu Artesona (DFT) [94,[98][99][100][101][102][103][104], with a special mention to the works of Pederson and Neese with di↵erent approaches to the zero-field splitting (ZFS) and the variants proposed to treat the spin-orbit coupling (SOC). Wave function based methodologies [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] have also been widely applied to TM-3d complexes and Ln-based systems. The scheme proposed by Maurice to extract the ZFS and the magnetic anisotropy using the e↵ective Hamiltonian theory and the work of Chibotaru that calculates the anistropic magnetic properties directly from the matrix elements ofL andŜ to a posteriori definition of the pseudospin Hamiltonians are two relevant works in multiconfigurational background.…”
Section: Theoretical Studies Of the Magnetic Properties Of Molecule-bmentioning
confidence: 99%